Development of Situational Judgment Test (SJT) Instrument to Measure the Employability Skills of Graduates - Mohd Hafiz, Zakaria (2013)
Globalization makes graduate recruitment for an organization more complex. Employers believe that a competitive workforce is the key to success of an organization. Currently, although graduates are said to have good specific skills, they still have problems with employability skills, and these problems affect the quality of their work. A good level of employability skills is essential in order to ensure that graduates are ready before entering the work market. Therefore, their level of employability skills should be evaluated. In this study, an instrument of employability skills for Universiti Utara Malaysia graduates across various fields was developed by using the assessment approach of situational judgment test (SJT). Twelve (12) items were developed measuring communication skill, professional ethics and morality, entrepreneurial skill, critical thinking in problem solving and personal quality. Instrument's validity was achieved through expert opinion and the reliability (in terms of stability) was based on the Chi-Square for homogeneity test and Mann-Whitney U test. Next, the validated instrument was used to obtain norm scores for each tested skill using the Bias-Corrected and Accelerated (BCA) bootstrap. The norm scores indicated that the respondents possessed a high level of professional ethics and morality; and a moderate level for other tested skills. Based on the findings, the instrument produced can be used by graduates, university, employers, government agencies and career development agencies when evaluating the level of employability skills.